Determination of working length for teeth with wide or immature apices: a review - Kim, Y.-J. A.; Chandler, N. P. (International endodontic journal, 2013)
Practitioners face several challenges during the root canal treatment of teeth with wide or immature apices, one of which is working length determination. There is relatively little data regarding the value of radiography and electronic apex locator (EAL) use when root formation is incomplete, and supplementary measurement techniques may be helpful. This review considers length determination for canals with wide or completely open apices in permanent and primary teeth. The Ovid Medline, Web of Science and Scopus databases were searched individually and in combinations to August 2012 using the subject headings ‘working length determination’ and ‘open apex’ and revealed only one article. Further headings, ‘tooth apex’, ‘apical constriction’, ‘resorption’, ‘foramen size’, ‘mature root apex’, ‘immature root apex’, ‘working length determination’, ‘apexification’, ‘open apices’, ‘open apex’, ‘open apical foramina’, ‘canal length determination’, ‘immature teeth’, ‘apical diameters’, ‘electronic apex locators’, ‘primary teeth’, ‘treatment outcome’ and ‘clinical outcome’ were entered. Potentially useful articles were chosen for a manual search of bibliography as well as a forward search of citations. Other investigations revealed case reports and some research related to open apices and laboratory studies evaluating EALs, radiography and tactile methods. Some involved permanent teeth of various apical diameters and primary teeth with and without resorption. There is a need to define the term ‘open apex’. Clinicians should be aware of the benefits and limitations of all canal measuring techniques involved in managing this problem.